View and perspective of the Trinity Church in Vienna - Unknown:::Creator:::::::::::: (Basset, Rue St. Jacques; Paris; France)
Color vue d'optique engraving of the Kirche zur heiligen Dreifaltigkeit in Vienna, with caption La Trinitè a Viene printed in mirror image at top of print